2002
DOI: 10.1164/rccm.200203-191oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combining Salmeterol and Fluticasone on the Progression of Airway Remodeling

Abstract: In subjects insufficiently controlled with low to moderate doses of inhaled corticosteroids, adding beta-agonists is clinically more beneficial than increasing the dose of inhaled corticosteroids. In the present study, we investigated the effect of adding salmeterol to fluticasone on allergen-induced airway inflammation and remodeling. Sensitized rats, in which characteristics of remodeling had been induced by ovalbumin exposure every 2 days from Days 14 to 28, were further exposed to ovalbumin or PBS from Day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…Failure of long acting β2 agonists (formoterol) to improve remodeling in the current study agrees with a previous study which showed that in OVA -sensitized and -challenged BALB/c mice, LABA treatment (salmeterol) exaggerated airway inflammation, remodeling, and hyperresponsiveness due to mucus metaplasia, while fluticasone separately or combined with salmeterol reduced airway inflammation and remodeling [10].Moreover, aerosolized combined salmeterol and fluticasone in rats reversed goblet cell hyperplasia, but increased fibronectin and collagen in the airway wall [23]. In addition, in asthmatic patients adding salmeterol to ICS reduced airway muscular tone and improved expiratory flows, but exerted a little effect on remodeling shown by decreasing number of vessels in the airway lamina propria [24].…”
Section: Discussionsupporting
confidence: 91%
“…Failure of long acting β2 agonists (formoterol) to improve remodeling in the current study agrees with a previous study which showed that in OVA -sensitized and -challenged BALB/c mice, LABA treatment (salmeterol) exaggerated airway inflammation, remodeling, and hyperresponsiveness due to mucus metaplasia, while fluticasone separately or combined with salmeterol reduced airway inflammation and remodeling [10].Moreover, aerosolized combined salmeterol and fluticasone in rats reversed goblet cell hyperplasia, but increased fibronectin and collagen in the airway wall [23]. In addition, in asthmatic patients adding salmeterol to ICS reduced airway muscular tone and improved expiratory flows, but exerted a little effect on remodeling shown by decreasing number of vessels in the airway lamina propria [24].…”
Section: Discussionsupporting
confidence: 91%
“…Treatment with fluticasone during this last 2 weeks of allergen challenge inhibits the additional increase in collagen deposition [43]. It is of interest that combining salmeterol with fluticasone during the last 2 weeks of this rat asthma model results in increased airway wall thickness and deposition of collagen and fibronection in the lungs [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, LABA is not primarily an antiinfl ammatory drug, and does not appear to have any clinically important anti-infl ammatory or proinfl ammatory effect (Sindi et al, 2009). Furthermore, the effect of LABA on airway remodeling remains controversial (Orsida et al, 2001;Vanacker et al, 2002). Thus, LTRA or theophylline as the add-on medication to ICS should be reconstructed.…”
Section: Discussionmentioning
confidence: 99%